Influence of pH on the activity of finafloxacin against extracellular and intracellular Burkholderia thailandensis, Yersinia pseudotuberculosis and Francisella philomiragia and on its cellular pharmacokinetics in THP-1 monocytes. (September 2020) - Chalhoub, H.; Harding, S.V.; Tulkens, P.M.; Van Bambeke, F.
Abstract: Objectives: Burkholderia pseudomallei, Yersinia pestis and Francisella tularensis are facultative intracellular bacteria causing life-threatening infections. We have (a) compared the activity of finafloxacin (a fluoroquinolone in development showing improved activity at acidic pH) with that of ciprofloxacin, levofloxacin and imipenem against the extracellular and intracellular (THP-1 monocytes) forms of infection by attenuated surrogates of these species ( B. thailandensis, Y. pseudotuberculosis, F. philomiragia ) and (b) assessed finafloxacin cellular pharmacokinetics (accumulation, distribution, efflux). Methods: Bacteria in broth or in infected monocytes were exposed to antibiotics at pH 7.4 or 5.5 for 24 hr. Maximal relative efficacies ( E max ) and static concentrations ( C s ) were calculated using the Hill equation (concentration–response curves). Finafloxacin pharmacokinetics in cells at pH 7.4 or 5.5 was investigated using 14 C-labelled drug. Results: Extracellularly, all drugs sterilized the cultures, with finafloxacin being two to six times more potent at acidic pH. Intracellularly, E max reached the limit of detection (4–5 log10 cfu decrease) for finafloxacin against all species, but only against B. thailandensis and F. philomiragia for ciprofloxacin and levofloxacin, while imipenem caused less than 2 log10 cfu decrease for all species. At acid pH, C s shifted to two to five times lower values for finafloxacin and to one to four times higher values for the other drugs. Finafloxacin accumulated in THP-1 cells by approximately fivefold at pH 7.4 but up to 20-fold at pH 5.5, and distributed in the cytosol. Conclusions: Fluoroquinolones have proven to be effective in reducing the intracellular reservoirs of B. thailandensis, Y. pseudotuberculosis and F. philomiragia, with finafloxacin demonstrating an additional advantage in acidic environments.